ABCF ATPases Involved in Protein Synthesis, Ribosome Assembly and Antibiotic Resistance: Structural and Functional Diversification across the Tree of Life. Issue 18 (23rd August 2019) - Murina, Victoriia; Kasari, Marje; Takada, Hiraku; Hinnu, Mariliis; Saha, Chayan Kumar; Grimshaw, James W.; Seki, Takahiro; Reith, Michael; Putrinš, Marta; Tenson, Tanel; Strahl, Henrik; Hauryliuk, Vasili; et al.
Abstract: Within the larger ABC superfamily of ATPases, ABCF family members eEF3 in Saccharomyces cerevisiae and EttA in Escherichia coli have been found to function as ribosomal translation factors. Several other ABCFs including biochemically characterized VgaA, LsaA and MsrE confer resistance to antibiotics that target the peptidyl transferase center and exit tunnel of the ribosome. However, the diversity of ABCF subfamilies, the relationships among subfamilies and the evolution of antibiotic resistance (ARE) factors from other ABCFs have not been explored. To address this, we analyzed the presence of ABCFs and their domain architectures in 4505 genomes across the tree of life. We find 45 distinct subfamilies of ABCFs that are widespread across bacterial and eukaryotic phyla, suggesting that they were present in the last common ancestor of both. Surprisingly, currently known ARE ABCFs are not confined to a distinct lineage of the ABCF family tree, suggesting that ARE can readily evolve from other ABCF functions. Our data suggest that there are a number of previously unidentified ARE ABCFs in antibiotic producers and important human pathogens. We also find that ATPase-deficient mutants of all four E. coli ABCFs (EttA, YbiT, YheS and Uup) inhibit protein synthesis, indicative of their ribosomal function, and demonstrate a genetic interaction of ABCFs Uup and YheS with translational GTPase BipA involved in assembly of the 50S ribosome subunit. Finally, we show that the ribosome-binding resistance factor VmlR from Bacillus subtilis is localized to the cytoplasm, ruling out a role in antibiotic efflux. Graphical Abstract: Unlabelled Image Highlights: We present a comprehensive classification of known and novel ABCFs across all life. We predict multiple novel subfamilies of antibiotic resistance ABCFs in pathogens. ATPase-deficient mutants of the four Escherichia coli ABCFs disrupt protein synthesis. Two E. coli ABCFs interact genetically with the ribosome assembly GTPase BipA. ARE ABCF VmlR is localized to the cytoplasm, ruling out a role in antibiotic efflux.